A new fossil species of Callipteris (Callipteridae) in the Early Permian from the Xishan Area in Beijing, North China - Chen, Xin-Yu; Zhang, Hua-Chuan; Yang, Jin-Yue (Phytotaxa, 2024)
A new early Permian Medullosa (Pteridospermatophyta) is described based on a moderately well-preserved sample from Xishan Area in Beijing, North China. Callipteris seshufenensis Chen sp. nov. represents the first record of genus Callipteris in the early Permian period in Beijing region. Callipteris seshufenensis has a remarkable morphology characterized by a narrow midvein with distinct transverse stripes, small pinnules with 2–3 lateral branches directly connected with pinna-rachis except for the rounded-obtuse apex of pinnule and costule divided more than three times (sometimes more than five times). Together with coeval callipterid fossils recorded from the North China plate and the Siberian plate, the present discovery suggests that the migration route of callipterids in China extended from West China to Northeast China.